POLICY ANALYSIS: IMPLEMENTATION OF MBKM IN HIGHER EDUCATION - Muhammad Redha; Zulfatmi (Jurnal Ikhtibar Nusantara, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) policy is a fundamental breakthrough in Indonesia's higher education system that aims to transform the conventional learning paradigm into a more flexible, innovative, and high-quality education. This study aims to analyze the implementation, challenges, and policies of MBKM in higher education institutions through a qualitative approach using a literature review method. The results of the study show that MBKM provides significant benefits in expanding student learning opportunities, improving graduate competencies, and building creativity and independence. However, the implementation of MBKM also faces a number of challenges, such as expanding communication, improving facilities, and adapting policies at the university level. Nevertheless, MBKM is expected to bring positive energy to the world of higher education in Indonesia by giving students a more active role and autonomy in their learning. Further research is needed to gain a deeper understanding of the effectiveness and efficiency of MBKM implementation in the context of Indonesian higher education.